P01.106 Impact of intraoperative magnetic resonance imaging on the extent of resection and functional outcome in awake surgery for eloquent gliomas - a single center retrospective study. (19th September 2018) - Jungk, C; Scherer, M; DaoTrong, H; Schramm, C; Haehnel, S; Herold-Mende, C; Unterberg, A
Abstract: Background: Maximizing the extent of resection (EOR) while preserving functional integrity is a mainstay of modern glioma surgery. Resection guidance tools such as intraoperative MRI (iMRI) help to augment the EOR. However, in eloquently located gliomas the significance of iMRI is controversial since the EOR is limited by functional rather than image-based boundaries. Thus, we set out to determine the impact of iMRI in our series of awake glioma resections. Methods: Our institutional database was searched for all awake glioma resections within or adjacent to eloquent (language, motor, sensory) areas since the implementation of a 1.5 Tesla iMRI in 2009. Demographic, tumor- and procedure-related data and functional outcome were assessed through medical charts review. The EOR was determined volumetrically on pre-, intra- and early postoperative T1 contrast-enhanced (CE) and FLAIR MR images. Results: In a 7-year period, awake surgery was performed in 104 glioma patients of whom 86 had iMRI-guided surgery with concurrent language (n=72) and/or motor (n=50) mapping. The iMRI group consisted of 53 lower-grade gliomas and 33 glioblastomas with a median age of 47 years (range 12–74), mainly located in left-sided language or motor areas (n=73; 85%). iMRI was well tolerated by all patients and was done when functional boundaries were reached (n=26; 30%), for resection control (n=53; 62%) or for other reasons (n=7). Additional resection after iMRI (AR) was performed in 63 cases (73%); otherwise resection was terminated because either the targeted EOR or functional boundaries were reached. New or deteriorated neurological deficits occurred in 20 patients prior (23%) and 15 patients post (17%) iMRI; however, all but 3 resolved within 6 months (3%). Median EOR significantly increased after AR from 92.6% to 98.4% (∆5.8%; p<0.0001) when CE was the target volume and from 64.5% to 85.8% (∆21.3%; p<0.0001) in non-enhancing tumors. Remarkably, the reason to perform iMRI, either for resection control or because of functional limitations, did not affect the frequency of AR, deficits acquired post iMRI or the increase in EOR after AR. Also, AR did not increase the rate of neurological deficits in the early or late postoperative course. Conclusion: IMRI is feasible in awake surgery of eloquently located gliomas and is a valuable adjunct to maximize the EOR without increasing the risk for functional impairment, particularly in non-enhancing tumors. Importantly, iMRI contributes to a maximized EOR even in cases where the resection has to be stopped because functional boundaries were reached.